Diamond Fraud Analysis in Detect Financial Statement Fraud in LQ45 Company List on The Indonesia Stock Exchange 2018-2020 - Lina Wulandari; Setianingrum, Hj. Nurul; Pratiwi, Angrum (Journal of Islamic Economics Perspectives, 2023)
LQ45 company is a company that collects 45 certain stocks with high liquidity level and adequate market capitalization. The purpose of this study is to detect the occurrence of fraudulent financial statements through the perspective of diamond fraud in LQ45 companies listed on the Indonesia Stock Exchange in 2018-2020. Indications of financial statement fraud in this study are proxied by earnings management which is measured using the Modified Jones model. The method used in this research is literature study and documentation. The sample in this study was decided by using the purposive sampling method from LQ45 companies listed on the Indonesia Stock Exchange during 2018-2020, resulting in a total of 66 company observations. The data analysis used in this research is multiple linear regression analysis. The results of this study indicate that the pressure and rationalization variables have no partial effect on financial statement fraud. While the opportunity and capability variables have no partial effect on financial statement fraud. Simultaneously, diamond fraud has a significant effect on financial statement fraud.